19.4k views
0 votes
−13 = 5(1 + 4m) − 2m multi step equation show all steps pls

2 Answers

6 votes

Answer:

m = -1

Explanation:

-13 = 5(1 + 4m) - 2m

Step 1 : Distributive Property

-13 = 5 + 20m - 2m

Add like terms

-13 = 5 + 18m

Subtract 5 on both sides

-18 = 18m

Divide


(-18)/(18) =
(18m)/(18)

m = -1

User Amna Ahmed
by
5.5k points
4 votes

Answer:

m = -1

Explanation:

Order of Operations: BPEMDAS

Step 1: Write out equation

-13 = 5(1 + 4m) - 2m

Step 2: Parenthesis (distribute)

-13 = 5 + 20m - 2m

Step 3: Combine like terms (m)

-13 = 5 + 18m

Step 4: Subtract 5 on both sides

-18 = 18m

Step 5: Divide both sides by 18

-1 = m

Step 6: Rewrite

m = -1

User Travis Leleu
by
5.8k points